A critical review on pyrolysis method as sustainable conversion of waste plastics into fuels. (1st April 2023) - Radhakrishnan, K.; Senthil Kumar, P.; Rangasamy, Gayathri; Praveen Perumal, L.; Sanaulla, S.; Nilavendhan, S.; Manivasagan, V.; Saranya, K.
Graphical abstract: Highlights: Pyrolysis as sustainable method for conversion of waste plastics into fuels. Summary on plastic wastes and different pyrolysis methods. Discussion on various critical parameter that affect the recycling process. Making use of the char and gaseous and by-products of pyrolysis. The technique might be useful to recycle mass-produced plastics. Abstract: Plastic production has increased globally, and many of these plastic items are no longer in use. The plastic wastes end up as garbage, disposed of in landfills, or scattered, posing major health and environmental risks. In terms of sustainability, converting plastic trash into fuels or any other better option, individual monomers, is a far more environmentally friendly waste management option than landfill dumping. Nearly 1.3 billion metric tonnes of plastic are produced annually as businesses strive to meet the demands of consumers. Plastic is made through a process called polymerization, in which hydrocarbons are rearranged into new molecules. These hydrocarbons often have a high molecular mass, and they may also contain other chemicals to boost their performance. Plastic is a useful material because, among other things, it is durable, lasts a long time, is inexpensive, and has many other benefits. Because plastic can take decades to degrade if left alone, effective waste plastic disposal should be a top priority for every-one. Yet, growing industrialization and urbanization have contributed to a discernible rise in fuel demand. Finding renewable energy sources to replace fossil fuels is now a critical global priority. Plastics-to-gasoline conversion provides a means to solve both of these problems. By applying intense heat (more than 370 °C) and an oxygen-free environment, pyrolysis thermochemically decomposes organic materials. The byproducts of pyrolysis are carbon black, hydrocarbons, and pyrolysis oil. This review focuses on pyrolysis as it is the most popular and efficient method for turning polymers into fuels in comparison with other methods. This review comprises the knowledge of different types of plastics and their properties. The major discussion was focused on pyrolysis methods for recycling plastics. To have better knowledge competitive recycling method were discussed. The optimization parameter for recycling process, by-products of plastics, advantages and disadvantages of pyrolysis process are discussed to identify the drawbacks and research gaps. The pyrolysis method are potential for addressing waste plastic management and highlights the need for a reliable alternative fuel source.